Factors influencing digital adoption in the family business: A conceptual framework - Nyayu Lathifah Tirdasari (Journal of Management and Digital Business, 2026)
The increasing prevalence of digital technologies has transformed business operations, offering both opportunities and challenges. Family businesses, as key contributors to the global economy, face unique challenges in digital adoption due to their distinctive structural and cultural characteristics. Despite their significance, limited research has explored how these enterprises navigate digital transformation. This study conducted a systematic literature review and bibliometric analysis of 23 peer-reviewed articles retrieved from Scopus. It identifies the critical factors influencing digital adoption in family businesses. It also proposes a conceptual framework comprising four key propositions, including entrepreneurial orientation as a driver of digital adoption, dynamic capabilities as enablers of successful digital transformation, family business culture as a central influence on digital adoption, and trust as a determinant of effective digital integration. The findings highlight the potential of digitalization to enhance operational efficiency, competitiveness, and community engagement in family businesses. This study contributes to the literature on digital adoption in family businesses and offers practical insights for enterprises embarking on digital transformation.